Life Skills Education Based on Local Excellence: Studi of State Special Schools Students in East Kalimantan - Rahmawati, Indriana; Basith, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The research was conducted to find out the application and implementation of life skills education, as well as the supporting and inhibiting factors for the implementation of Life Skills Education conducted by SLBN in East Kalimantan. Life skills education is very important for students with special needs. With life skills education, it is hoped that it can eliminate socio-economic disparities and minimize discrimination that students with special needs often experience. The type of research used is qualitative research with a descriptive approach. Collecting research data using interviews, observation, and documentation Primary data sources are skills-coordinating teachers, school principals, and students. Furthermore, the data obtained will be tested for validity using triangulation techniques and analyzed using multi-site analysis techniques developed by collecting, reducing, presenting, and drawing conclusions. The research results that have been found are as follows: Live skills education has an important role in the life development of SLB students; full support is needed to increase competency. This will have a big impact, especially on social life. With the provision of skills, SLB students can strive to improve their standard of living. Applicable skills such as sewing, hydroponic gardening, cooking or processing food from ingredients that are easily obtained from seafood, agriculture, and plantations in the surrounding environment, as well as creating goods from materials that are easy to obtain. At the same time, they are given the skills to market their work to other people and the public. All of these activities can help students grow and develop in parallel. The realization of these live skills education activities must also get support from various parties. Both parents, the government, teachers, and, of course, the wider community serve as users, or the community serves as facilitators.